Bridging The Knowledge-Behaviour-Injury Divide: A Comparative Systematic Literature Review of Agricultural Occupational Safety Training in Developed and Developing Contexts - Daniel Tafuma; Baiduri Widanarko (Riviera Publishing, 2026)
Agricultural safety training is widely used to reduce occupational injuries and pesticide-related morbidity. However, whether knowledge gains lead to sustained behavioral change and measurable injury reduction remains uncertain, particularly across different regulatory and structural contexts. This research aimed to synthesize evidence on the effectiveness of agricultural occupational safety training in developed and developing settings and to examine outcomes along the knowledge–behavior–injury pathway. This review followed the PRISMA 2020 guidelines. Searches were conducted in PubMed, ScienceDirect, and Google Scholar using terms such as agricultural safety, occupational safety training, knowledge–behavior translation, injury prevention, and safety behavior. Studies underwent title/abstract and full-text screening using predefined criteria. Exclusions included gray literature, conference abstracts, editorials, non-English studies, non-agricultural contexts, publications below Q2 ranking, and articles without verifiable DOI or PMID identifiers. The review was registered on the Open Science Framework. Educational interventions consistently improved safety knowledge across contexts. Behavioral outcomes were moderate and context-dependent, with stronger effects observed in participatory or structurally supported interventions. Evidence linking training alone to sustained injury reduction was limited. A clear attenuation pattern was observed from knowledge acquisition to behavioral change and injury outcomes. Psychosocial factors were key moderators in developed settings, while structural constraints were more influential in developing contexts. Agricultural safety training improved knowledge but showed reduced impact on behavior and injury outcomes when implemented alone. A systems-oriented approach is needed, integrating education with regulatory, structural, and behavioral reinforcement to achieve sustainable injury prevention.